(untitled) (Third Sector Social Economic Review, 2026)
This study aims to examine how eHealth literacy varies across generations and to do so using both parametric analyses and data-driven classification methods. The study used data collected via a survey from 561 participants across the X, Y, and Z generations living in Istanbul. First, an ANOVA was conducted to examine variation in eHealth literacy across generations. Subsequently, K-means cluster analysis was performed to investigate how eHealth literacy clustered within the data. In the final stage, cross-tabulation and chi-square analysis were used to test the significance of the relationship between the resulting clusters and the generations. The ANOVA results showed a significant difference between generations. Generation X had lower eHealth literacy scores than other generations; no significant difference was observed between Generations Y and Z. The cluster analysis identified three clusters of eHealth literacy: low, medium, and high. The chi-square test revealed a significant relationship between generations and clusters. Generation X was mainly represented in the medium-low eHealth literacy cluster, Generation Y was primarily described in the medium eHealth literacy cluster, and Generation Z was mainly represented in the high eHealth literacy cluster. The findings show that eHealth literacy differs significantly across generations. Generation Z stands out as the group with the highest eHealth literacy, while Generation X has relatively lower eHealth literacy. The results indicate that differentiated approaches are necessary in the design of generation-based digital health education and eHealth applications.